PENILAIAN TERHADAP SIFAT-SIFAT FISIKA DAN KIMIA TANAH SERTA KUALITASNYA PADA LAHAN SAWAH MARJINAL - Latief Mahir Rachman; Fahrizal Hazra; Rahma Anisa (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
Various efforts have been carried out by the Indonesian Government to increase rice production, especially the construction of new paddy fields and paddy intensification through increasing intensity or planting frequency in a year. Overcoming the problems of chemical and physical soil properties that have caused low soil productivity is an effort that can be made to increase rice production. This study was aimed to assess the quality of soil physical and chemical properties of the paddy fields in order to find out the cause of the low productivity of paddy soils. The study was conducted in 24 locations in Banten and West Java Provinces. In general, based on their soil quality indexes, the study found that the soil physical quality of paddy soil is good and better than soil chemical quality. There was no significantly different between soil physical quality of paddy soil in Banten and West Java Provinces. However, the soil chemical quality of paddy soils in West Java Province is significantly better than in Banten Province. There were no limiting factors for soil physical properties, while in some locations, some limiting factors of soil chemicals properties were found. Dominant limiting factors for plant growth were the low available P, organic matter and total organic N contents, low pH, and low exchangeable K, and high level of Fe.